Metrik Finsler Pseudo-Konveks Kuat pada Bundel Vektor Holomorfik - Haripamyu ,; Jenizon ,; I Made Arnawa (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2017)
Abstract: Rizza-negativity of holomorphic vector bundle is a sufficient condition for the negativity of . In the present paper, we shall discuss that as a special case, using the Rizza metric which is derived from a Hermitian metric also implies the negativity of . Further we showed that for the negative holomorphic vector bundle there is a pseudo-convex Finsler metric with negative curvature. Keywords: Hermitian metric, Rizza metric, Rizza-negativity.